Challenges facing the implementation of Chemistry and Physics as separate and stand-alone subjects in the revised Secondary School curriculum in Malawi: A Case Study of Blantyre District - Vizyalona, Arthur; Chirwa, Grames Wellington; Nyoni, Precious (International Journal of Educational Innovation and Research, 2024)
It is impossible to overestimate the importance of chemistry and physics to society, but in Malawi, secondary schools do not adequately teach these subjects. The purpose of this study is to investigate the obstacles to the efficient teaching of physics and chemistry and to suggest ways to improve their application. Using Cornbleth's framework for curricular implementation as a guide, the study looks into the challenges instructors in these areas confront. The qualitative case study, which took place in two secondary schools in Malawi's Blantyre District, involved 28 participants which were two head teachers, three chemistry teachers, three physics teachers, and twenty students. Data was collected through classroom observations in addition to interviews. The results show that there are a number of issues, such as a lack of certified teachers, inadequate resources and labs, a dearth of textbooks, inadequate teacher orientation, poor teaching and evaluation techniques, and a lack of supervision. To improve Chemistry and Physics education in secondary schools, recommendations include hiring more trained instructors, constructing well-equipped laboratories, and enhancing teacher preparation and oversight.